2023
DOI: 10.1002/art.42722
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis Progression in the APPLE Trial Can Be Predicted in Young People With Juvenile‐Onset Systemic Lupus Erythematosus Using a Novel Lipid Metabolomic Signature

Junjie Peng,
Pierre Dönnes,
Stacy P. Ardoin
et al.

Abstract: ObjectivesPatients with juvenile‐onset systemic lupus erythematosus (JSLE) have increased atherosclerosis risk. This study investigated novel atherosclerosis progression biomarkers in the APPLE trial, the largest investigator‐led randomised control trial of atorvastatin versus placebo for atherosclerosis progression in JSLE, using carotid intima‐media thickness (CIMT) as primary outcome.MethodsUnsupervised clustering of baseline CIMT and CIMT‐progression over 36 months was used to stratify JSLE patients. Disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…2 Although very few CYP with cSLE have been stratified as having high CVD-risk by any of the CVD-risk scores used in the APPLE cohort at baseline, we also assessed stratification performance of these scores at the end of the APPLE trial (36 months) in the placebo versus statin arm. As the metabolomic signature of atherosclerosis progression we discovered did not predict the CIMT progression in response to statin, we used the rates of CIMT progression over 36 months in each arm 5 for stratification. As expected, all CVD-risk scores underperformed at the end of the trial as they did at baseline and failed to identify individuals with high CIMT progression rates, irrespective of the treatment arm allocation (online supplemental table).…”
Section: Lupus Science and Medicinementioning
confidence: 99%
See 2 more Smart Citations
“…2 Although very few CYP with cSLE have been stratified as having high CVD-risk by any of the CVD-risk scores used in the APPLE cohort at baseline, we also assessed stratification performance of these scores at the end of the APPLE trial (36 months) in the placebo versus statin arm. As the metabolomic signature of atherosclerosis progression we discovered did not predict the CIMT progression in response to statin, we used the rates of CIMT progression over 36 months in each arm 5 for stratification. As expected, all CVD-risk scores underperformed at the end of the trial as they did at baseline and failed to identify individuals with high CIMT progression rates, irrespective of the treatment arm allocation (online supplemental table).…”
Section: Lupus Science and Medicinementioning
confidence: 99%
“…4 Although the trial did not meet the primary endpoint, it provided us with the opportunity to discover a novel serum metabolomic signature associated with a high rate of atherosclerosis progression in cSLE. 5 As CIMT measurements on vascular scans are not routinely implemented in clinical practice, we explored the comparative performance of four age-appropriate and validated CVD-risk scores in a global cSLE (UK/ US) cohort to address a key research priority identified by our PPIE activities.…”
mentioning
confidence: 99%
See 1 more Smart Citation